Microstructure and mechanical properties of HA/Ti composite coatings applied by detonation spraying - Ж.Б. Сағдолдина; Д.Р. Байжан; Б.К. Рахадилов; Д.Б. Буйткенов; Н.Е. Бердімуратов; М.С. Жапарова (Қарағанды университетінің хабаршысы. Физика сериясы)
This work presents the results of experimental studies of the structure and mechano-tribological properties of composite coatings based on hydroxyapatite (HA) and titanium in different ratios (wt. %): 30HA-70Ti, 50HA-50Ti, 70HA-30Ti. Composite coatings with a thickness of 40-50 μm were applied to a substrate made of Grade 2 titanium by detonation spraying. Microstructures and phase compositions of as-sprayed coatings were analyzed by scanning electron microscopy and X-ray diffraction. The deposition mechanism of HA-Ti composite coatings was also examined. The results of the study showed that during detonation powder spraying from a mixture of HA-Ti, porous coatings are formed, consisting of the phases of hydroxyapatite Ca10(PO4)6(OH)2, tricalcium phosphate, titanium, and titanium oxide. It was found that with a decrease in the content of hydroxyapatite in the composite, there is a decrease in the relative content of B-type carbonate ions in the structure, as well as a decrease in the content of the mineral phase as a whole. Composite coating 30HA-70Ti wt. % is the closest in structure to stoichiometric crystalline HA (Ca/P = 1.67). At ratios of coatings 50HA-50Ti wt. %, an increase by 1.5-2 times in wear resistance is observed.